Preliminary karyotype analysis of Amolops panhai and Sylvirana nigrovittata (Anura, Ranidae) from southern Thailand - Waranee Pradit (2018)
© 2017, Archana Sharma Foundation of Calcutta. Karyotype and ideogram analyses of Somsak’s cascade frog (Amolops panhai) and dark-sided frog (Sylvirana nigrovittata), collected from Nakhon Si Thammarat Province, southern Thailand, were performed. Chromosomes were prepared from the intestinal epithelium and stained by conventional Giemsa staining. From this study, we found that A. panhai possesses the diploid chromosome number of 26 (2n = 26), while the chromosome number of S. nigrovittata is 24 (2n = 24). This is the first report on karyotype of A. panhai, containing 10 pairs of metacentric (m), 2 pairs of submetacentric (sm) and 1 pair of subtelocentric (st) chromosomes with the arm number of 52. The S. nigrovittata’s karyotype contains 12 pairs of chromosomes with the arm number of 48 in only the metacentric form. The karyotype formulae could be represented as 2n (26) = 10m + 2sm + 1st and 2n (24) = 12m for A. panhai and S. nigrovittata, respectively.